Hemophagocytic lymphohistiocytosis associated with SFTS virus infection: A case report with literature review. Issue 31 (August 2016) - Oh, Hong Sang; Kim, Moonsuk; Lee, Jeong-Ok; Kim, Haeryoung; Kim, Eu Suk; Park, Kyoung Un; Kim, Hong Bin; Song, Kyoung-Ho
Abstract: Background: Severe fever with thrombocytopenia syndrome (SFTS) is a new emerging zoonosis. Hemophagocytic lymphohistiocytosis (HLH) is a life-threatening syndrome caused by hyperinflammation. Here, we report the case of SFTS-associated HLH. Case summary: A 62-year-old man was admitted to local hospital with 8 days of fever and chill. He had leukopenia, thrombocytopenia, and developed seizure. An attending physician examined bone marrow to rule out hematologic malignancy. He was transferred to tertiary referral hospital for suspicious HLH. We decided to confirm its histologic feature for sure. Bone marrow and liver biopsy showed hemophagocyotic histiocytes. Serological tests for other infections were all negative except SFTS virus polymerase chain reactions (PCRs) as positive from serum, bone marrow, bronchoalveolar lavage fluid, and liver biopsy specimen. A definitive diagnosis was SFTS-associated HLH. During 2 weeks of conservative treatment, he succeeded in recovery from multiple organ failure. Conclusion: SFTS should be considered one of differential diagnosis of HLH. In certain endemic areas, SFTS infection deserves clinicians' attention because it can be presented hematologic diseases as HLH.